Radiological and histological assessment of a novel interlocking three-dimensional miniplate for mandibular angle fractures: an animal study - Kreshanti, Prasetyanugraheni; Noviana, Deni; Priosoeryanto, Bambang Pontjo; Kekalih, Aria; Rahyussalim; Supriadi, Sugeng; Hatibie, Mendy Juniaty; Sukasah, Chaula Luthfia (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Open reduction and internal fixation are considered the gold standard for managing mandibular fractures, as they effectively restore anatomical structure and functionality. Three-dimensional (3D) miniplates were developed to obtain a geometrically stable structure. However, the rigid structure of 3D miniplate may cause screw holes to be located within the fracture lines or directly above important anatomical structures. Hence, we have developed customizable interlocking 3D miniplates that allow for modifications in the configuration of the horizontal miniplates and vertical cross-struts to meet specific requirements. METHODS This study included 24 goats divided into 2 groups: interlocking 3D miniplate and standard plate. Each group was further divided into subgroups sacrificed on Days 5, 28, and 56. Radiological assessments were performed to evaluate bone, muscle, peri-implant bone, and peri-implant muscle density. Histological assessments were performed using Masson's trichome (MT) for bone healing evaluation and hematoxylin and eosin (H&E) staining for biocompatibility. RESULTS Radiological assessment indicated an increase in density across all measured parameters from Day 5 to 56. Histological evaluation from MT staining showed a significantly higher fibrocartilage in the interlocking 3D miniplate group (6.109%, IQR 1.453–10.828) compared to standard plate (1.311%, IQR 0.636–2.553; p = 0.001). Furthermore, H&E staining showed significantly higher inflammatory cell counts in the standard group on Days 28 and 56 compared to the interlocking 3D miniplate group (p = 0.027). CONCLUSIONS This study concluded that the interlocking 3D miniplate showed better bone healing properties and biocompatibility than the standard plate.